2016
DOI: 10.1016/j.chemosphere.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated and methoxylated polybrominated diphenyl ethers in long-tailed ducks (Clangula hyemalis) and their main food, Baltic blue mussels (Mytilus trossulus × Mytilus edulis)

Abstract: Long-tailed ducks (Clangula hyemalis) that breed in northern Europe and western Siberia and commonly winter in the Baltic Sea, are threatened by a significant population decrease. The ducks are, by primarily feeding on Baltic blue mussels (Mytilus trossulus × Mytilus edulis) while wintering in the Baltic Sea, potentially subjected to high levels of toxic hydroxylated polybrominated diphenyl ethers (OH-PBDEs). To assess long-tailed ducks exposure to polybrominated phenols (PBPs), polybrominated anisoles (PBAs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…[6][7][8][9][10][11][12]36 BPs and OH-BDEs are partially ionized at seawater pH, 37,38 but are nevertheless subject to bioaccumulation. 24,28,39 Diverse toxic effects of 2,4,6-triBP 40 and OH-BDEs [18][19][20] have been reported, and benecial antimicrobial activity has been attributed to 6-MeO-BDE47. 41 Many studies have demonstrated interconversion of BPs/BAs and OH-BDEs/MeO-BDEs through O-methylation/ demethylation reactions, 18,19,40 and it has been suggested that wildlife acquire OH-BDEs through O-demethylation of accumulated MeO-BDEs.…”
Section: Papermentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12]36 BPs and OH-BDEs are partially ionized at seawater pH, 37,38 but are nevertheless subject to bioaccumulation. 24,28,39 Diverse toxic effects of 2,4,6-triBP 40 and OH-BDEs [18][19][20] have been reported, and benecial antimicrobial activity has been attributed to 6-MeO-BDE47. 41 Many studies have demonstrated interconversion of BPs/BAs and OH-BDEs/MeO-BDEs through O-methylation/ demethylation reactions, 18,19,40 and it has been suggested that wildlife acquire OH-BDEs through O-demethylation of accumulated MeO-BDEs.…”
Section: Papermentioning
confidence: 99%
“…Macroalgae and cyanobacteria are important sources of bromophenolic compounds to the Baltic ecosystem and they are transferred through the food web from macroalgae to invertebrate grazers to sh. 24 Several studies have reported bromophenolic compounds in Baltic mussels, which lter-feed on cyanobacteria 8,10,21,[28][29][30] and transferred from mussels to seaducks. 28 Macroalgae from the Nordic coastal region are being promoted as human food, with published recipes utilizing local species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The width of the diamond is proportional to the size of the sample (i.e., the amount of animals belonging to the group) whole fish from the Baltic proper, both in perch (Perca fluviatilis, 6.6 ng/g w.w.) [31], and in herring (0.49 ng/g w.w.) [29]. However, the levels were higher than the reported liver concentration in long-tailed duck from the Baltic proper (0.24 ng/g w.w.) [32].…”
Section: Quantitative Analysesmentioning
confidence: 99%
“…Blood from these birds was only used for method evaluation, and no quantitative data for HPCs have been published (Dahlberg et al 2014). However, quantitative data for HPCs in the livers from the long-tailed ducks have been published (Dahlberg et al 2016). Herring (Clupea harengus) and flounder (Platichthys flesus) plasma collected at the Askö marine research station in May and June of 2011 were also remains from previous studies; no data have been published on these samples.…”
Section: Samplesmentioning
confidence: 99%